1985
DOI: 10.1136/pgmj.61.713.239
|View full text |Cite
|
Sign up to set email alerts
|

Six year remission of ACTH-dependent Cushing's syndrome using bromocriptine

Abstract: Summary A patient with ACTH-dependent Cushing's syndrome remained in clinical and biochemical remission six years after pituitary irradiation and while on bromocriptine therapy. When bromocriptine was discontinued urinary free cortisol values became elevated, and were not suppressed by dexamethasone. After reintroduction of the drug, remission was again obtained. It is concluded that bromocriptine is responsible for continuing longterm remission in this case. The possible use of bromocriptine as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Pharmacological agents directed at ACTH secretion in Cushing's disease are rarely of value. There have been sporadic reports of the use of cyproheptadine and bromocriptine in hypercortisolism (Krieger et al, 1975;Lamberts et al 1980b;Atkinson et al, 1985a;Whitehead et al, 1990). In our recent experience we have found that neither cyproheptadine nor bromocriptine, nor a combination of the two, effectively reduces ACTH secretion following bilateral adrenalectomy (Whitehead et al, 1990), and we have also founa them ineffective in cases of cyclical Cushing's syndrome (Atkinson et al, 1985b).…”
Section: Drug Therapymentioning
confidence: 80%
“…Pharmacological agents directed at ACTH secretion in Cushing's disease are rarely of value. There have been sporadic reports of the use of cyproheptadine and bromocriptine in hypercortisolism (Krieger et al, 1975;Lamberts et al 1980b;Atkinson et al, 1985a;Whitehead et al, 1990). In our recent experience we have found that neither cyproheptadine nor bromocriptine, nor a combination of the two, effectively reduces ACTH secretion following bilateral adrenalectomy (Whitehead et al, 1990), and we have also founa them ineffective in cases of cyclical Cushing's syndrome (Atkinson et al, 1985b).…”
Section: Drug Therapymentioning
confidence: 80%
“…[78][79][80][81] Bromocriptine has been reported to be successful in cases associated with both normal and elevated serum prolactin levels. [82][83][84][85][86][87][88][89] However, it is possible that publication bias towards reports of success may skew the overall picture and no controlled trials have been published. Invitti et al .…”
Section: Dopamine Agonists and Serotonin Antagonistsmentioning
confidence: 99%
“…However, trials in series of consecutive patients revealed that only fewer than 25% of unselected patients respond to bromocriptine. A clinical response to low-dose (less than 10 mg) bromocriptine in 15 cases has been reported thus far (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), while tumor shrinkage has been reported in only 3 cases (9,16,18) (Table 2).…”
Section: T a B L E 2 Re P O R T E D Ca S E S O F Cu S H I N G ' S Dmentioning
confidence: 97%